Європейський контекст "українського авангарду": між мистецтвом та ідеологією - Ковбасюк, С. (Київський національний університет імені Тараса Шевченка, 2016)
This article looks at the Ukrainian avant-garde's ways of development in the European context. We focused mainly on the role of the political factor in the avant-garde artistic evolution. European sources of the Ukrainian avant-garde are revealed as well as the ideological basis and several features of formation and functioning of the two centres of art education in Germany and Ukraine (the "Bauhaus" school and the Kyiv Art Institute). We also analyse the main reasons of the persecution of avant-garde artists in the Nazi Germany and the totalitarian Soviet Union. As we have found out, the Ukrainian avant-garde as the Ukrainian Baroque style in the XVIIth century, was a vivid manifestation of a European civilization choice, which in 1930 was suppressed by the Soviet authorities. This kind of relationships' evolution between artists and authorities was also characteristic for the "Bauhaus" school as in times of the relative flexibility of the Soviet power and the "golden 20s" of the Weimar Republic avant-garde and politics were inseparable, complementing and supporting each other. When to replace the existing power structures came totalitarian regimes, avant-garde artists were persecuted or forced to emigrate. Their art was condemned as "a degenerate" as in the Nazi Germany, so in the Soviet Union. Instead of Cubism, Constructivism, Suprematism and Сubo-Futurism came totalitarian aesthetics – "social realism ", which for decades affirmed as the party approved, official art.

У цій статті аналізується шляхи розвитку мистецтва "українського авангарду" у європейському контексті. Особлива увага була присвячена розкриттю ролі політичного фактору в художній еволюції авангарду. Послідовно розкриваються європейські витоки українського авангарду, порівнюються ідейна основа та особливості формування і функціонування двох осередків мистецької освіти в Німеччині та Україні (школа "Баухаус" та Київський художній інститут), аналізуються причини переслідування художників авангардистів у нацистській Німеччині та тоталітарному Радянському Союзі. Встановлено, що український авангард, як колись до того українське бароко, був яскравим проявом європейського цивілізаційного вибору, який у 1930-тих роках був придушений радянською владою. Ця еволюція стосунків, властива і для розглянутого нами "Баухаусу", дуже характеристична: у часи відносної гнучкості радянської влади та "золотих 20-тих" Веймарської республіки, авангард та політика були нероздільні, доповнюючи та підтримуючи одне одного. Коли ж на зміну існуючим владним структурам прийшли тоталітарні режими, митці авангарду були репресовані, або змушені емігрувати. Їх мистецтво було засуджене як "дегенеративне" і в нацистській Німеччині, і в Радянському союзі. На зміну кубізму, конструктивізму, супрематизму та кубофутуризму прийшла тоталітарна естетика – "соц. реалізм", який на довгі десятиліття ствердився в якості партійно схваленого, офіційного мистецтва.
Ukrainian avant-garde in the European context: between art and ideology
Keywords: Ukrainian avant-garde; Bauhaus; Constructivism; Cubo-Futurism; Suprematism; український авангард; Баухаус; конструктивізм; кубофутуризм; супрематизм